2009
DOI: 10.1016/j.amepre.2009.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Physical, Consumer, and Social Aspects of Measuring the Food Environment Among Diverse Low-Income Populations

Abstract: Obesity and other diet-related chronic diseases are directly related to the food environment. We describe how to better assess the food environment in specific ethnic minority settings for designing and implementing interventions, based on a review of our previous work on the food environment in American Indian reservations, Canadian First Nations reserves, the Republic of the Marshall Islands, and inner-city Baltimore. The types of food stores available within each setting and the range of healthy foods avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
73
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(80 citation statements)
references
References 31 publications
3
73
0
4
Order By: Relevance
“…Future qualitative research is warranted to investigate the spatial boundaries community members use to define their local food environment. 32 Finally, while all of the participants shopped at the Boys and Girls Club farmers' markets, we do not know where they purchased the majority of their foodstuffs. Thus, we do not know if the local food environment is the only food access point or if participants travel to other environments to gain access to healthier foods.…”
Section: Limitationsmentioning
confidence: 98%
“…Future qualitative research is warranted to investigate the spatial boundaries community members use to define their local food environment. 32 Finally, while all of the participants shopped at the Boys and Girls Club farmers' markets, we do not know where they purchased the majority of their foodstuffs. Thus, we do not know if the local food environment is the only food access point or if participants travel to other environments to gain access to healthier foods.…”
Section: Limitationsmentioning
confidence: 98%
“…As a subversive movement, the practice of UA generally increases social capital, civic involvement, community efficacy, and empowerment (Armstrong, 2000;Ferris, Norman, & Sempik, 2001;Gittelsohn & Sharma, 2009;Teig et al, 2009). In addition, studies have identified public participation as a crucial component of the food security planning process (Jacobsen, Pruitt-Chapin, & Rugeley, 2009;McCullum, Desjardins, Kraak, Ladipo, & Costello, 2005;Vasquez, Lanza, Hennessey-Lavery, Facente, Halpin, & Minkler, 2007).…”
Section: Ua and Food Justicementioning
confidence: 99%
“…Access to healthy foods has many dimensions including physical access (having food in geographic proximity given transportation options), economic access (having sufficient resources to pay for food), nutritional access (having access to food that is of good nutritional value) and cultural access (having food that is culturally appropriate) (3)(4)(5) .…”
mentioning
confidence: 99%